About the Computational Prediction of the Maximum Absorption Wavelengths of Indigo in Different Solvents with the Minnesota Family of Density Functionals - Norma Flores-Holguin; Juan Frau; Daniel Glossman-Mitnik (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
This research reports the results of the use of the Minnesota family of density functionals (M05, M05-2X, M06, M06L, M06-2X and M06-HF) for the calculation of the UV-Vis of the Indigo molecule in solvents of different polarities using Time-Dependent Density Functional Theory (TD-DFT) and the Polarized Continuum Model (PCM). The maximum absorption wavelengths predicted for each density functional on every solvent were compared with the known experimental results.